Application of The Haversine Method In The Android-Based Donation Search Application - Daniel Daniel; Desiyanna Lasut (bit-Tech, 2023)
Used goods that we no longer use will only fill the room which if we leave it will be damaged and have no use value because it consumes time. If given to someone else, the goods may still be useful and can help their lives the problem is how we find people who need our goods and vice versa. For this reason, a system is needed that can help facilitate and bring the two parties together. The effort made to make it easier for the recipient to contribute in taking the donated goods is to use the haversine method so that the recipient can consider the distance between them and the donated item. The haversine formula is an equation that uses latitude and longitude to find the distance between the two different points. By using the haversine formula, the output is the distance from the location of the party receiving the donation (current location) to the donor. Therefore, the author wants to create and design an android-based application so that it can reach many people and can make it easier for donors to donate their goods or for the recipient of donations in looking for items that have been donated.